Effects of a medication reminder calendar on medication compliance in older adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Greyvenstein, June Barbara (Massey University, 2001)
The present study aimed to investigate whether the provision of an individualised medication reminder calendar would improve medication compliance, by acting as a cognitive aid for older adults, who may be suffering the mild memory deficits which tend to be the usual concomitants of normal ageing. The present study also examined medication compliance and error rates and their relationship with the amount of daily medication taken by participants, as well as with selected demographic and socio-economic factors. A convenience sample of community dwelling participants (N = 50), aged between 55 and 84 years (M = 71) who were prescribed an average of five daily medications, was randomly assigned to either calendar or control groups. Medication compliance was assessed via two pill counts conducted, on average, seven and a half weeks apart. The results showed that participants using the calendar and those in the control group did not differ in terms of compliance measures. The average rate of compliance with medication for the sample was 97%. The mean number of errors made by participants during the interval between pill counts was 19 (79% errors of omission and 21% errors of commission). Multivariate analysis indicated that the number of daily tablets taken was positively associated with the number and types of errors made. Women were less compliant than men, while participants of lower socioeconomic status made more errors of commission. Discussion of these results focused on the non-representativeness of the sample and the difficulties associated with obtaining volunteers. Possible directions for future medication compliance research were discussed.
Keywords: Self medication; Older people; Drug use; Medication errors